Medication-Related Complaints in Residential Aged Care - Juanita L. Breen; Kathleen V. Williams; Melanie J. Wroth (Pharmacy, 2023)
Complaints reflect a person’s or family’s experience within the aged care system and provide important insight into community expectations and consumer priorities. Crucially, when aggregated, complaints data can serve to indicate problematic trends in care provision. Our objective was to characterize the areas of medication management most frequently complained about in Australian residential aged care services from 1 July 2019 to 30 June 2020. A total of 1134 complaint issues specifically referenced medication use. Using content analysis, with a dedicated coding framework, we found that 45% of these complaints related to medicine administration processes. Three categories received nearly two thirds of all complaints: (1) not receiving medication at the right time; (2) inadequate medication management systems; and (3) chemical restraint. Half of the complaints described an indication for use. These were, in order of frequency: ‘pain management’, ‘sedation’, and ‘infectious disease/infection control’. Only 13% of medication-related complaints referred to a specific pharmacological agent. Opioids were the most common medication class referred to in the complaint dataset, followed by psychotropics and insulin. When compared to complaint data composition overall, a higher proportion of anonymous complaints were made about medication use. Residents were significantly less likely to lodge complaints about medication management, probably due to limited engagement in this part of clinical care provision.